Dynamics of Bipartite Vibrational Entanglement under the Inherent Decoherence Process in $H_2O$ (Journal of Atomic and Molecular Sciences, 2016)
In present study, the dynamics of stretching-stretching and stretching-bendingentanglement in $H_2O$ are studied with considering the inherent decoherence process.It is shown that the excitation in the bending vibration can lead to the decreaseof the generation rate of stretching-stretching entanglement for the non-superposedstate and the degeneration of entanglement for the initial entangled states. For specificinitial entangled states, the stretching-stretching entanglement can live for a long time,and the correspondence between energy transfer and entanglement is still maintainedfor the initial local mode states. For the stretching-bending vibrations, the stretching-bendingentanglement is much lower than the stretching-stretching vibration, andthe degeneration rate of stretching-bending entanglement is higher than that of thestretching-stretching entanglement. The excitation in the remaining stretching vibrationcan induce a higher degree of stretching-bending entanglement.
Keywords: bipartite vibrational entanglement; inherent decoherence process; Lie algebraic method for molecular vibration